The impact of automatic video auditing with real-time feedback on the quality and quantity of handwash events in a hospital setting - Lacey, Gerard (My University, 2020)
Background: Poor quality handwashing contributes to the spread of nosocomial infections. We investigate the impact of automatic video auditing (AVA) with feedback on the quality and quantity of handwashing in a hospital setting. Methods: AVA systems were mounted over all handwash sinks in a surgical unit. Phase 1 established baseline handwashing quality and quantity. Phase 2 examined the impact of real-time performance feedback, and phase 3 examined the incremental impact of weekly team performance reports. Phase 4 remeasured the baseline without feedback. Results: A total of 3,606 handwash events were audited. During phase 2 and 3, compliance with the World Health Organization technique improved from 15.7%-46% (P < .0001), and the average number of handwash events per patient per day increased from 0.91-2.25 (P < .0001). Performance returned to baseline in phase 4. Conclusions: AVA with real-time feedback significantly improved the quality and quantity of handwashing. The combination of AVA with electronic monitoring will allow simultaneous auditing of hand hygiene quantity and quality. The impact of cognitive offloading onto the technology may have contributed to the return to baseline at the end of the study, and suggests further research is required in this area.
PUBLISHED
Keywords: Handwashing; Training; Feedback; IT for infection control; Image processing; Artificial intelligence